EFFECTIVENESS OF CYROMAZINE APPLICATION AND PARASITOIDS RELEASE FOR CONTROLLING AGAINST LEAFMINER FLY Liriomyza huidobrensis (BLANCHARD) (DIPTERA: AGROMYZIDAE) - Warsito Tantowijoyo (Widyariset, 2011)
Liriomyza huidobrensis is an invasive pest for various crops. Till now, the management of this pest is by the only use of pesticides which hence increased its resistance and decrease of its natural enemies. The objective of the study was to assess the effectiveness of cyromazine and parasitoids for reducing the population of leafminer ﬂ y (L. huidobrensis) and to analyse the economic impact of the different treatments. The study was conducted in the Sirukem village, Kalibening sub district, Banjarnegara district, Central Java from July to November 2009. To address the objective, four treatment strategies were applied: no treatment, cyromazine, parasitoid release and cyromazine-parasitoid, and observa-tion of damage intensity, sampling of infested leaves, assessment of yield and an economic analysis were undertaken. The results found that cyromazine and parasitoids were effective to control against infestation of Liriomyza. Cyromazine was also harmless for parasitoids. The dominant parasitoid found were Opius chromatomyiae and Hemiptarsenus varicorni which preferred to parasitize the larvae of L.huidobrensis on Vicia faba than on Solanum tuberosum.